Smart grid load management driven by IoT-based Arduino R4 controller (Journal of Academic Research, 2026)
The increasing global demand for renewable energy and the critical need for efficient power management have made the development of innovative load management solutions necessary. This paper proposes an Internet of Things (IoT)-based Arduino R4 controller for load management in a smart grid. The system is designed to optimise energy consumption by providing real-time monitoring and control over the renewable energy sources and the utility grid. The technical approach involves integrating the Arduino with current and voltage sensors to track the power of PV, battery, utility grid and load consumption. Collected data is then transmitted to a cloud platform for detailed analysis and visualisation, supporting better decision-making and efficient load management. The monitoring components for the proposed system are low-cost and readily available on the market.
Keywords: load management; PV panel, battery; smart grid; Arduino; Keywords— Smart Buildings, Internet of Things (IoT), Cisco Packet Tracer, Remote Control Systems, Home Automation